The influence of chronic diseases on the manifestation of COVID-19 infection - S.O. Yastremska; Olha M. Krehkovska-Lepiavko; Borys A. Lokay; O. Bushtynska; S.V. Danchak (Вісник медичних і біологічних досліджень, 2021)
The first known case of infection from the novel coronavirus was recorded almost one year ago, in China’s Hubei province. The city of Wuhan was infamous the world over as the original virus epicenter, seeing more than half of China’s reported cases and deaths. The outbreak of COVID-19 virus, as sickened more than 14.7 million people. At least 610.200 people have died. The aim of the study – to analyze and systematize the literature data about the influence of chronic diseases on the manifestation of COVID-19 infection. Materials and Methods. The study uses publications of the world scientific literature on COVID-19 infection, in particular the causes and mechanisms of its development, treatment, complications and its consequences as well as the influence of different chronic disorders on the course of COVID-19. Results. A sample of patients hospitalized with COVID-19 across 14 states of the USA in March was analyzed by The Centers for Disease Control and Prevention. It was found that many (89 %) had underlying health problem and 94 % of patients were at the age 65 and older. The case fatality rate for those under age 60 was 1.4 percent. For those over age 60, the fatality rate jumps to 4.5 percent. The older the population, the higher the fatality rate. For those 80 and over, Covid-19 appears to have a 13.4 percent fatality rate. Moreover, it was recognized, that older adults don't present in a typical way of the course of different disorders, and we're seeing that with Covid-19 as well. Conclusions. Chronic diseases and conditions are on the rise worldwide. COVID-19 became the most challenging pandemic influencing all countries worldwide. Chronic diseases are suggested to be one of the main causes of different life-threatening complications of COVID-19 infection and one of the main factors of poor prognosis for the patients